Confronting the smart city governance challenge - MORA, Luca (Institutional Knowledge at Singapore Management University, 2025)
Governance inefficiencies threaten the potential of smart city projects to deliver equitable urban transformations. Current strategies often hinder implementation, and risk harmful technological effects on communities. Tackling this challenge demands urgent reforms to better integrate scientific insights into smarter governance practices.